2013
DOI: 10.2903/j.efsa.2013.3079
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on application (EFSA‐GMO‐NL‐2010‐87) for the placing on the market of genetically modified herbicide tolerant oilseed rape GT73 for food containing or consisting of, and food produced from or containing ingredients produced from, oilseed rape GT73 (with the exception of refined oil and food additives) under Regulation (EC) No 1829/2003 from Monsanto

Abstract: This scientific opinion is a risk assessment for the placing on the market of the genetically modified (GM) herbicide-tolerant oilseed rape (OSR) GT73 for food containing or consisting of, and food produced from or containing ingredients produced from, OSR-GT73. OSR-GT73 contains a single insert consisting of the goxv247 and CP4 epsps expression cassettes. Both proteins confer tolerance against glyphosate-based-herbicides. Bioinformatic analyses of inserted DNA and flanking regions did not raise safety concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 68 publications
(86 reference statements)
9
16
0
Order By: Relevance
“…Analyses of the amino acid sequence of the newly expressed CP4 EPSPS and GOXv247 proteins show no relevant similarities to toxins or allergens. In addition, bioinformatic analyses of the newly created ORFs within the insert or spanning the junctions with genomic DNA confirm previous conclusions indicating no similarities to toxins or allergens for the event GT73 (EFSA, 2004;EFSA GMO Panel, 2009, 2013.…”
Section: Evaluation Of the Updated Bioinformatic Datasupporting
confidence: 82%
See 1 more Smart Citation
“…Analyses of the amino acid sequence of the newly expressed CP4 EPSPS and GOXv247 proteins show no relevant similarities to toxins or allergens. In addition, bioinformatic analyses of the newly created ORFs within the insert or spanning the junctions with genomic DNA confirm previous conclusions indicating no similarities to toxins or allergens for the event GT73 (EFSA, 2004;EFSA GMO Panel, 2009, 2013.…”
Section: Evaluation Of the Updated Bioinformatic Datasupporting
confidence: 82%
“…The updated bioinformatic analysis for oilseed rape event GT73 does not reveal any DNA sequence that could provide sufficient length and identity which could facilitate double homologous recombination (HR), confirming the previous conclusions (EFSA, 2004;EFSA GMO Panel, 2013). Given the results of this analysis and the potential of the recombinant DNA in oilseed rape GT73 to confer selective advantages or increased fitness to microorganisms, the GMO Panel identified no safety concern linked to an unlikely but theoretically possible HGT.…”
Section: Evaluation Of the Updated Bioinformatic Datasupporting
confidence: 76%
“…The GMO Panel assessed these data for possible new hazards, modified exposure or new scientific uncertainties identified during the authorisation period and not previously assessed in the context of the original application. Under the assumption that the DNA sequences of the events in oilseed rape GT73 considered for renewal are identical to the sequences of the originally assessed event, the GMO Panel concludes that there is no evidence in the renewal application EFSA‐GMO‐RX‐026/1 for new hazards, modified exposure or scientific uncertainties that would change the conclusions of the original risk assessment on oilseed rape GT73 (EFSA GMO Panel, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…oilseed rape: oilseed rape. materials and consequently human exposure would have been much greater than from the oil, the GMO Panel considered that a more extensive toxicological assessment of the protein was necessary in the context of application EFSA-GMO-NL-2010-87 (EFSA GMO Panel, 2013). To this end, a 28-day toxicity study in rodents was requested.…”
Section: Introductionmentioning
confidence: 99%
“…The applicant argued that such a study was not needed to confirm the safety of GOXv247 protein 7 and did not provide the study. Consequently, the GMO Panel concluded that, in the absence of consumption data and repeated dose toxicity studies with the GOXv247 protein, it was not in the position to complete the risk assessment of products of this nature (EFSA GMO Panel, 2013).…”
Section: Introductionmentioning
confidence: 99%